Pertanggungjawaban Notaris terhadap Covernote: Analisis Inkonsistensi Judisial dalam Putusan Nomor 4242 K/PID.SUS/2023 - Alika Puteri Handaka; Jeanette Emmanuelle Gozali; Qinaya Putri Kusuma (Eksekusi : Jurnal Ilmu Hukum dan Administrasi Negara, 2026)
This research focuses on the criminal liability of Notary Dewi Farni Dja'far (the Defendant) in the criminal case concerning corruption relating to the granting of a Refinancing Investment Loan (KIR) by PT Bank Negara Indonesia (BNI) to PT Barito Riau Jaya. The legal issue lies with the Defendant in issuing a number of letters of certification or cover notes, stating that the process of obtaining certificates for 502 (five hundred and two) plots of land used as collateral was underway at her office. However, in reality, the land parcels, which were still based on Land Certificates (SKT), were problematic and could not be upgraded to Certificates of Ownership and Certificates of Right to Use, meaning the bank disbursed the loan without valid collateral. The Defendant’s actions are deemed to have assisted the debtor Esron Napitupulu (Director of PT Barito Riau Jaya) in securing the loan, resulting in a financial loss to the state amounting to Rp22,650,000,000.00. The results of this study indicate that, based on Article 16 of Law No. 2 of 2014 amending Law No. 30 of 2004 on the Office of the Notary, a Notary is liable under civil law (compensation), criminal law (offences), and administrative law (code of ethics) if found to have committed a breach in the performance of their duties. The objective of this study is to analyse the liability of notaries regarding covernote in problematic credit agreements. The research method employed is normative in nature, with a descriptive qualitative approach. Data sources were obtained from court decisions, legislation, and other supporting sources.